2008
DOI: 10.1186/1471-244x-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Family violence, war, and natural disasters: A study of the effect of extreme stress on children's mental health in Sri Lanka

Abstract: Background: The consequences of war violence and natural disasters on the mental health of children as well as on family dynamics remain poorly understood. Aim of the present investigation was to establish the prevalence and predictors of traumatic stress related to war, family violence and the recent Tsunami experience in children living in a region affected by a long-lasting violent conflict. In addition, the study looked at whether higher levels of war violence would be related to higher levels of violence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
325
4
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(352 citation statements)
references
References 36 publications
17
325
4
6
Order By: Relevance
“…Among these risk factors, pre-existing child characteristics (e.g., gender, age, and prior exposure to traumatic events) have been well studied. Many studies found that girl survivors of disasters had a greater risk than boy survivors to develop PTSD and depressive symptoms [8,[17][18][19], although some studies did not find significant gender differences [18,20]. With regard to the association between age and PTSD symptoms, the results have been inconsistent across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Among these risk factors, pre-existing child characteristics (e.g., gender, age, and prior exposure to traumatic events) have been well studied. Many studies found that girl survivors of disasters had a greater risk than boy survivors to develop PTSD and depressive symptoms [8,[17][18][19], although some studies did not find significant gender differences [18,20]. With regard to the association between age and PTSD symptoms, the results have been inconsistent across studies.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing girls and boys, previous studies have shown that girls are more likely than boys to develop PTSD symptoms following disaster exposure (Garrison et al, 1995; Giannopoulou et al, 2006; John et al, 2007), although some studies find no such difference (Catani et al, 2008). We did not compare girls and boys regarding prevalence of symptoms, but our gender stratified analyses indicate that both genders show increased risk of symptoms of anxiety or worries but only boys show headache(s) and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies on children’s well-being following natural disasters have focused on post-traumatic stress disorder (PTSD) (Bokszczanin, 2007; Catani, Jacob, Schauer, Kohila, & Neuner, 2008; Fan, Zhang, Yang, Mo, & Liu, 2011; Goenjian et al, 2011; John, Russell, & Russell, 2007; Lai, Kelley, Harrison, Thompson, & Self-Brown, 2015; Self-Brown, Lai, Thompson, McGill, & Kelley, 2013; Stanke, Murray, Amlot, Nurse, & Williams, 2012). Depression and anxiety have also been reported among children post-disaster, and are often comorbid with PTSD (La Greca, Silverman, Lai, & Jaccard, 2010; Lai, La Greca, Auslander, & Short, 2013; Swenson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is understandable because a nuclear accident has a broader range of impact compared to natural disasters through air and water leakages, transportation of people, and food supplies. Although proximity could be a moderator, studies that compared the impact of natural and human-related extreme-stress disasters (Catani et al 2008) on young people's well-being are scarce. Therefore, the extent to which proximity to the disaster site influences young people's mental health when the disaster is a multilevel incident (i.e., both natural and human-related) is unclear.…”
Section: Introductionmentioning
confidence: 99%